The Effect of Using Nutritional – Physical Program on Health Related Fitness components and Losing Weight in Obese Women Aged (25 – 35) Years Old - Ayad, Amena; Abdul Nebi, Hameed (Journal of Physical Education, 2020)
The problem of the research lies in women wanting to lose weight yet unable to maintain a healthy nutritional program along with the physical program. The research aimed at designing a nutritional – physical program for obese women as well as identifying its effect on health-related fitness development and losing weight in obese women. The researchers used the experimental program on (6) obese women aged (25 – 35) years old from the nutritional researchers’ institute in the specialized clinic for treating obesity. The training program lasted for three sessions per week for two months to conclude that the program has a positive effect on improving health relate fitness and losing weight. Finally, the researchers recommended decreasing calories and increasing training load gradually through repetitions in future athletic programs.